Novel Human Neutral Sphingomyelinase 2 Inhibitors as Potential Therapeutics for Alzheimer's Disease - Šála, Michal; Hollinger, Kristen R; Thomas, Ajit G; Dash, Ranjeet P; Tallon, Carolyn; Veeravalli, Vijayabhaskar; Lovell, Lyndah; Kögler, Martin; Hřebabecký, Hubert; Procházková, Eliška; Nešuta, Ondřej; Donoghue, Amanda; et al. (Journal of medicinal chemistry, 2020)
Neutral sphingomyelinase 2 (nSMase2) catalyzes the cleavage of sphingomyelin to phosphorylcholine and ceramide, an essential step in the formation and release of exosomes from cells that is critical for intracellular communication. Chronic increase of brain nSMase2 activity and related exosome release have been implicated in various pathological processes, including the progression of Alzheimer's disease (AD), making nSMase2 a viable therapeutic target. Recently, we identified phenyl (R)-(1-(3-(3,4-dimethoxyphenyl)-2,6-dimethylimidazo[1,2-b]pyridazin-8-yl)pyrrolidin-3-yl)carbamate 1 (PDDC), the first nSMase2 inhibitor that possesses both favorable pharmacodynamics and pharmacokinetic (PK) parameters, including substantial oral bioavailability, brain penetration, and significant inhibition of exosome release from the brain in vivo. Herein we demonstrate the efficacy of 1 (PDDC) in a mouse model of AD and detail extensive structure-activity relationship (SAR) studies with 70 analogues, unveiling several that exert similar or higher activity against nSMase2 with favorable pharmacokinetic properties.
Keywords: exozómy; sfingomyelinfosfodiesterasa; myši transgenní; Disease Models, Animal; mužské pohlaví; Sphingomyelin Phosphodiesterase; Alzheimer Disease; mozek; Mice; Body Weight; Brain; modely nemocí na zvířatech; ženské pohlaví; pyridaziny; zvířata; vztahy mezi strukturou a aktivitou; Humans; tělesná hmotnost; Exosomes; myši; Pyridazines; Alzheimerova nemoc; Female; Structure-Activity Relationship; Mice, Transgenic; Enzyme Inhibitors; lidé; Male; inhibitory enzymů; Animals